NILAI-NILAI PENDIDIKAN ISLAM DALAM TAFSIR AHMAD MUSTHAFA AL-MARAGHI: STUDI ANALISIS TERHADAP AL-QUR’AN SURAT AL-FIIL - Loeis, Wisnawati (Turats, 2011)
The purpose of this paper is to analyze the educational values inherent in the Qur'an Surah Al-Fiil according to Tafsir Al-Maraghi. From this paper can be concluded that the Qur'an as the Muslim holy teachings, in that it contains clues towards a better life, to live how humans use it. Uninstalling the values in it means waiting for future destruction. Instead go back to the Qur?an means and the inner longing for peace was born, because the teachings contained in the Qur?an contains the peace. When the Muslims away from the Qur?an or simply making the Qur?an just as religious then it is definitely reading the Koran will lose its relevance to the realities of the universe. The Qur'an should be understood and practice. One effort to understand the Qur'an is to interpret. Tafsir Al-Maraghi is one interpretation that is easily understood and in it is loaded with educational value. Educational value of Surat Al-Fiil, among others, that we should learn from the events that befall those who passed away in which people who rebel against God as King Abraha will be destroyed by God. God will repay every human act good deeds both good and evil.